SIMULATION AND EXPERIMENTAL EVALUATION OF AN INNOVATIVE ROTARY COMPRESSOR WITH VARIABLE SPEED DISPLACERS - Kopelowicz, H. J.; Barreto, A. R.; Moutella, F. L. C.; Arêas, H. T.; Parise, J. A. R.; Siqueira, C. E. R. (Revista de Engenharia Térmica, 2008)
This paper describes preliminary studies of a new rotary compressor with variable speed displacers. Two displacers rotate concentrically, in an annular space, at variable and phased angular velocities, thus creating two variable-volume compression spaces between them. The displacers are individually driven by two concentric shafts. An innovative driving mechanism imposes phased variable angular speeds to the shafts and, consequently, to the displacers, thus providing a volume variation in the gas compression spaces. The driving mechanism also offers a convenient way of capacity control, from zero to 100%, at constant electric motor speed. A mathematical model simulating the performance was developed. A traditional simulation model for positive displacement compressors was employed, where mass and energy conservation equations, in differential form, were applied to the control volumes (two compression spaces). Uniformly distributed thermodynamic properties of gas, varying with time, were assumed for each control volume. Equations describing the volume variation with time, the gas to cylinder wall heat transfer and gas flow through valve ports and leakage passages were also employed. The resulting mathematical model was a system of ordinary differential equations, the numerical integration of which provides the time-history of pressure and temperature of the gas inside the compression chambers. A prototype was also constructed and tested. First performance results are presented, showing the compressor behaviour under different operational conditions.